Effects of replacing fishmeal with wastes derived from local fisheries on the growth of juvenile tilapia, Oreochromis niloticus - Chitmanat C. (2014)
A feeding trial was conducted to investigate the effects of partially and totally replacing fishmeal with by-product derived from local fisheries on growth performances of tilapia (Oreochromis niloticus). Tilapia fingerlings (average initial weight 0.38±0.05 g) were fed with 5 different diet formulas composing of fish meal protein replacement levels of 0%, 25%, 50%, 75, and 100%. Tilapia were raised in 80 x 80 x 80 cm3 hapa in an earthen pond for 8 weeks. Each treatment contained 3 replications. No feeding trial was applied as negative control. The result showed that fish by-product powder could substitute for fishmeal on a crude protein basis at a level of not more than 25%. As a result, feed cost can only be cut down approximately 3 US cents/kg. Specific growth rate, weight gain, survival rate and feed conversion ratio were not significantly different between the fish fed with the 75% and 100% fishmeal containing diets (P>0.05). The outcome would be applied to reduce the solid wastes from fish processing and partially replace the imported fishmeal. This can also be used as guideline for farmers in small communities to produce their own tilapia feed.